Variation in the ICAM1 gene is not associated with severe malaria phenotypes. - Fry, A; Auburn, S; Diakite, M; Green, A; Richardson, A; Wilson, J; Jallow, M; Sisay-Joof, F; Pinder, M; Griffiths, M; Peshu, N; Williams, T; et al. (2008)
Evidence from autopsy and in vitro binding studies suggests that adhesion of erythrocytes infected with Plasmodium falciparum to the human host intercellular adhesion molecule (ICAM)-1 receptor is important in the pathogenesis of severe malaria. Previous association studies between polymorphisms in the ICAM1 gene and susceptibility to severe malarial phenotypes have been inconclusive and often contradictory. We performed genetic association studies with 15 single nucleotide polymorphisms (SNPs) around the ICAM1 locus. All SNPs were screened in a family study of 1071 trios from The Gambia, Malawi and Kenya. Two key non-synonymous SNPs with previously reported associations, rs5491 (K56M or 'ICAM-1(Kilifi)') and rs5498 (K469E), were tested in an additional 708 Gambian trios and a case-control study of 4058 individuals. None of the polymorphisms were associated with severe malaria phenotypes. Pooled results across our studies for ICAM-1(Kilifi) were, in severe malaria, odds ratio (OR) 1.02, 95% confidence interval (CI) 0.96-1.09, P=0.54, and cerebral malaria OR 1.07, CI 0.97-1.17, P=0.17. We assess the available epidemiological, population genetic and functional evidence that links ICAM-1(Kilifi) to severe malaria susceptibility.